K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

15 tháng 10 2020

\(\left(x-1\right)\left(x+1\right)-3x-6=6\)    

\(x^2-1^2-3x-6-6=0\)   

\(x^2-1-3x-12=0\)   

\(x^2-3x-13=0\)   

\(\orbr{\begin{cases}x=\frac{3-\sqrt{61}}{2}\\x=\frac{3+\sqrt{61}}{2}\end{cases}}\)

15 tháng 10 2020

\(\left(x-1\right)\left(x+1\right)-3x-6=6\)

\(\left(x-1\right)\left(x+1\right)-3x=12\)

\(\left(x-1\right)x-\left(x-1\right)1-\left(1+2\right)x=12\)

\(\left(x-1-1+2\right)x-x-1=12\)

\(\left(x-1-1+2-1\right)x=11\)

\(\left(x-1\right)x=11\)

\(x^2-x=11\)

Đk : x > 4

\(x=4\Rightarrow16-4=11\left(\varnothing\right)\)

\(x\in\varnothing\)

15 tháng 10 2020

a^4+a^3+a^2+a=a^10

15 tháng 10 2020

a4 + a3 + a2 + a

= a3( a + 1 ) + a( a + 1 )

= ( a + 1 )( a3 + a )

= a( a + 1 )( a2 + 1 )

15 tháng 10 2020

Ta có: \(x^4+x^3+x^2-1\)

\(=x^3\left(x+1\right)+\left(x-1\right)\left(x+1\right)\)

\(=\left(x+1\right)\left(x^3+x-1\right)\)

15 tháng 10 2020

x4 + x3 + x2 - 1

= x3( x + 1 ) + ( x - 1 )( x + 1 )

= ( x + 1 )( x3 + x - 1 )

15 tháng 10 2020

a) 2x - x3 + 4y - 8y3

= ( 2x + 4y ) - ( x3 + 8y3 )

= 2( x + 2y ) - ( x + 2y )( x2 - 2xy + 4y2 )

= ( x + 2y )( 2 - x2 + 2xy - 4y2 )

b) -3x2 + 11x + 14

= -3x2 + 14x - 3x + 14

= -x( 3x - 14 ) - ( 3x - 14 )

= ( 3x - 14 )( -x - 1 )

15 tháng 10 2020

Sai đề bạn ơi

15 tháng 10 2020

3x (5x2 - 2x - 1)

15 tháng 10 2020

Bài 1:

a) \(3x^2-9x=3x\left(x-3\right)\)

b) \(x^2-4x+4=\left(x-2\right)^2\)

c) \(x^2+6x+9-y^2=\left(x+3\right)^2-y^2=\left(x-y+3\right)\left(x+y+3\right)\)

Bài 2: 

a) \(101^2-1=\left(101-1\right)\left(101+1\right)=102.100=10200\)

b) \(67^2+66.67+33^2=67^2+2.33.67+33^2\)

\(=\left(67+33\right)^2=100^2=10000\)

Bài 3:

\(x\left(x-3\right)+2\left(x+3\right)=0\)

\(\Leftrightarrow\left(x-3\right)\left(x+2\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x-3=0\\x+2=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=3\\x=-2\end{cases}}\)

Vậy \(x=-2\)hoặc \(x=3\)

15 tháng 10 2020

B1:

a) \(3x^2-9x=3x.\left(x-3\right)\)

b) \(x^2-4x+4=\left(x-2\right)^2\)

c) \(x^2+6x+9-y^2=\left(x+3\right)^2-y^2=\left(x+3+y\right).\left(x+3-y\right)\)

B2:

a) \(101^2-1=\left(101+1\right).\left(101-1\right)=102.100=10200\)

b) \(67^2+66.67+33^2=67^2+2.33.67+33^2=\left(67+33\right)^2=100^2=10000\)

B3:

\(x\left(x-3\right)+2\left(x-3\right)=0\)

\(\left(x-3\right).\left(x+2\right)=0\)

\(\Rightarrow\orbr{\begin{cases}x-3=0\\x+2=0\end{cases}\Rightarrow}\orbr{\begin{cases}x=3\\x=-2\end{cases}}\)

15 tháng 10 2020

Phân tích hả ?

1) ( x4 + 2 )2 - 8x4

= x8 + 4x4 + 4 - 8x4

= x8 - 4x4 + 4 = ( x4 - 2 )2

2) 9( x + 5 )2 - ( x + 7 )2

= 32( x + 5 )2 - ( x + 7 )2

= ( 3x + 15 )2 - ( x + 7 )2

= [ ( 3x + 15 ) - ( x + 7 ) ][ ( 3x + 15 ) + ( x + 7 ) ]

= ( 3x + 15 - x - 7 )( 3x + 15 + x + 7 )

= ( 2x + 8 )( 4x + 22 )

= 2( x + 4 )2( 2x + 11 )

= 4( x + 4 )( 2x + 11 )

3) 4a + 4ab6 + ab12

= a( 4 + 4b6 + b12 )

= a( 2 + b6 )2